Study of structural evolution and photoluminescent properties at room temperature of Ca(Zr, Ti)O-3 powders - Cavalcante, L. S.; Simões, Alexandre Zirpoli [UNESP]; Espinosa, J. W. M. [UNESP]; Santos, L. P. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Pizani, P. S. (Elsevier B.V. Sa, 2008)
Calcium zirconate titanate, Ca(Zr0.05Ti0.95)O-3 (CZT) powders has been synthesized by the polymeric precursor method. The structural evolution and analysis of the CZT powders were monitored by the X-ray diffraction (XRD), Fourier transform Raman spectroscopy (FT-Raman) and ultraviolet-visible absorption spectroscopy (UV-vis). The decomposition of precursor resin was accompanied by evolution of thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTA). UV-vis measurements suggested that the presence of intermediary energy levels in the band gap are favorable for the intense and broad photoluminescence (PL) in structurally disordered CZT powders at room temperature. TGA and DTA have been employed to correlate the ranges of temperature with the structural order-disorder degree in the CZT lattice that are responsible by PL emission. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: ceramics; chemical synthesis; order-disorder effects; thermal analysis; luminescence